Liberal, Malay and Malaysian writings of a walking contradiction - Zan Azlee (Gerakbudaya Enterprise, 2017)
For some people, to be Liberal, Malay and Malaysian is to be a walking contradiction, to be pulled in more directions than your body can take. If you're Malay you aren't supposed to be liberal and of course you must be a Malay before you're a Malaysian! Right? Not for Zan Azlee. In Liberal, Malay and Malaysian Zan passionately argues for a Malaysian and a Malay identity which moves beyond identity politics, fatwas, censorship and moral policing and which allows individuals to be who they want to be. Covering themes of politics, race, religion and protest, Zan records a nation in turmoil, caught between activism and apathy and counters this with an honest and open assessment of Malaysian life.